Composite wing flutter analysis with variations of ribs location - Zaki, Nurul Zubaidah (The Aeronautical and Astronautical Society of the Republic of China, 2020)
Elastic structures constructed using composite materials may be easily deformed due to low stiffness, leading to flutter phenomenon to occur during flight. In this paper, the occurrence of flutter on a composite UAV wing is investigated by considering the effect of the location and position of ribs on flutter speed. Flutter analyses are conducted using the full aeroelastic equation of motion derived from the Lagrange's equation and Theodorsen's airfoil theory. UTM CAMAR UAV composite wings are selected as case studies in which the ribs are positioned across the wing span to obtain the optimized rib position. The natural frequencies for bending and torsion at each of the rib positions is obtained using the finite element analysis, conducted using the ABAQUS software. From the study, a pair of ribs located at 33% and 67% of wing span was found to give the maximum flutter speed at 264.62 m/s.